Evaluation of the Cell Phone Microbial Contamination in Dental and Engineering Schools: Effect of Antibacterial Spray - Reihaneh Hosseini Fard; Raziyeh Hosseini Fard; Mohammad Moradi; Maryam Alsadat Hashemipour (Springer, 2018)
Introduction: The aim of this study was to evaluate the microbial contamination of cell phone in dental and engineering schools and also investigating the effect of an antibacterial spray. Method and Materials: A questionnaire was completed by participants, including the pattern of using mobile phones and their disinfection. The number of participants was 120 students and professors in each of dental and engineering schools. Swabs from mobile phones of the participants were taken and plated on culture medium. The t-test, Chi-Square with the SPSS 11.5 program were used in data analysis. Results: In total, 240 mobile phones were cultured for microorganisms, while 65.8% (n = 158) were culture-positive. One hundred percent of professors, 98% of students' dental school and 72% of professors and 62% of students of engineering, believe that mobile can serve as a source of pathogens. The most commonly cultured organisms were Staphylococcus Aureus, Escherichia coli, Enterococcus Faecalis, and Pseudomonas. The current study showed that none of the mobile phones of the professors and students of the engineering university was infected by Pseudomonas and Candida albicans. Conclusion: The results of this study showed that mobile phones may act as an important source of nosocomial pathogens.